RFID IoT-enabled warehouse for safety management using product class-based storage and potential fields methods. (2018) - Trab, Sourour; Bajic, Eddy; Zouinkhi, Ahmed; Abdelkrim, Mohamed Naceur; Chekir, Hassen
Security and risk management in warehouses and logistics is a key factor to achieve a sustainable and safe supply chain. The paper aims at proposing RFID-IoT-enabled warehouse management focused on safety assurance for goods and people leveraging product class-based storage (pCBS), communicating object, RFID and IoT components. Security issues between products, storage locations, transportation equipment, environment and people are handled with the use of potential fields methods associated with smart product management in RFID-IoT warehouse architecture. A dynamic calculation of suitable storage locations is proposed, founded on negotiation mechanisms between products and shelves and their availability and compatibility constraints according to pCBS method. A safe and secure product storage path discovery method is presented using attractive/repulsive potential fields for path minimisation while maximising security level along the way. A multi-agent-based simulation with NetLogo demonstrates the effectiveness of the proposal allowing to achieve safe warehouse management by using smart product reactivity against critical risks.